Phytotechnical performance of leafy vegetables under organic management with fermented agro-industrial composts in Brazil - Ana Amélia dos Santos Cordeiro; Ricardo Luiz Louro Berbara; José Guilherme Marinho Guerra; Luiz Fernando de Sousa Antunes; Giulia da Costa Rodrigues dos Santos; Ednaldo da Silva Araújo; José Antonio Azevedo Espindola (International Journal of Recycling of Organic Waste in Agriculture, 2025)
Purpose: This study evaluated how fermented agro-industrial bran composts, with or without T. asperellum inoculation, affect soil enzymatic activity and crop performance in successively grown American lettuce and bertalha under organic management at Fazendinha Agroecológica, Brazil.